Faktor-Faktor yang Memengaruhi Pemberian ASI Ekslusif di Kota Tasikmalaya - IMA KARIMAH; Irma Nuraeni (HB PRESS, 2023)
The coverage of exclusive breastfeeding in Indonesia is still relatively low. According to the 2021 Ministry of Health report, exclusive breastfeeding in Indonesia reached 69.7%. The coverage of exclusive breastfeeding in West Java is still below the national figure of 65.9%. Based on data from the Health Office of the City of Tasikmalaya in 2022, in Tasikmalaya the coverage of exclusive breastfeeding has been achieved and some has not been achieved. Cibeureum and Purbaratu Health Center have high coverage of exclusive breastfeeding. Bantar and Indihiang Health Center have exclusive breastfeeding coverage, which is still below the target. One of the factors influencing the low level of exclusive breastfeeding is the lack of family support. In addition, a mother's knowledge is also a determinant factor in exclusive breastfeeding. The study aimed to determine the factors that influence exclusive breastfeeding. The results of this study indicate that a husband's support was associated with exclusive breastfeeding. Toddlers who did not have a husband's support are 8,542 times more likely to receive exclusive breastfeeding than those who do have a husband's support. Meanwhile, the support of parents and in-laws is not related to exclusive breastfeeding. However, there were a tendency for respondents who receive exclusive breastfeeding to have greater support from their parents and in-laws. Exposure to information about exclusive breastfeeding was not related to exclusive breastfeeding. The results of the Kolmogorov-Smirnov test showed that there was no relationship between exclusive breastfeeding and the mother's knowledge.